MUHAMMADIYAH'S POLITICAL DIALECTICS IN INDONESIA - Nurul Ihza; Supri Supri; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This paper examines how the dynamics of the Miuhammadiyah politic in 1937-1942 with 2010-2014. The problem in this study is the difference in the political dynamics of Muhammadiyah during the KH. Mas Mansur 1937-1942 and in 2010-2014. The purpose of this paper is to determine the political dynamics of the leadership of KH. Mas Masnur and how the political dynamics in 2010 were declared to have started to depart from the original organizational goals of Muhammadiyah, which is a religious-based community organization that devotes its attention to the social and educational fields. This type of research is library research. The facts that the writer searches for are in the text or written sources; archives, books, magazines and other texts containing the political dynamics of Muhammadiyah. Qualitative descriptive research method. This journal is a conceptual journal taken from several sources and then put together. The results of this study are the political dynamics of the mihammadiyah, the involvement of Muhammadiyah in politics, the politically impressed movement that occurred during the tablig akbar